Peran Mediasi Keterlibatan Karyawan terhadap Kinerja Pekerjaan XYZ Hotel & Service Apartment - Luthfi Razan Priyangga; Arief Alfiandry (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This study aims to examine the effect of training and development and work-life balance on job performance, with employee engagement as a mediating variable. This study is motivated by the decline in employee performance and discipline at XYZ Hotel & Service Apartment. The method used is a quantitative approach with PLS-SEM analysis of 85 respondents. The results show that training, work balance, and employee engagement have a positive effect on job performance. Engagement also mediates the influence of the two independent variables on performance. The findings provide important implications for management in improving performance through targeted HR strategies. These results also offer broader theoretical and practical implications. From a theoretical perspective, this study strengthens human resource management literature by emphasizing the critical role of employee engagement as a mediating mechanism that connects organizational practices with performance outcomes. From a practical perspective, organizations are encouraged to design structured and continuous training programs, as well as implement policies that support work-life balance to enhance employee engagement. Furthermore, management should foster a supportive work environment, promote open communication, and provide fair evaluation and reward systems. These efforts are expected to improve employee motivation, reduce absenteeism, and ultimately enhance sustainable organizational performance in the service industry.